Recommendations for Strengthening the Hydraulic Calculation and Coastal River of the River in Amudarya with Adjusted Conditions - Ibragimov Ilhom Akhrorovich; Inomov Dilmurod Islom ugli; Yavov Aziz Uktam ugli (International Journal on Orange Technologies, 2021)
The article provides recommendations for hydraulic calculations and shore protection in the construction of protection and adjustment facilities to create safe conditions in the settlements along the river in the lower reaches of the Amudarya and to prevent flooding in arable lands. In our previous work, the morphological characteristics of the riverbed in the lower reaches of the Amudarya were studied, the calculated calculations were used and recommendations for the use of gabion structures to strengthen the river banks were developed.